Pre-writing Techniques for the Development of Logical Thinking of EFL University Students in Writing Argumentative Essays - Peggy Magdalena Jonathans; Utami Widiati (English Language Teaching and Research, 2020)
Writing an argumentative essay might put more challenges toEFL low proficient students. This paper seeks to shed light on the contribution of pre-writing techniques to the development of logical thinking expected in an argumentative essayamong Indonesian EFL university students. With two objectives leading the discussion, the paper suggests pre-planning to construct thinking while simulatenously reading going along with the writing as a source of input. Clustering and outlining, the proposed two pre-writing techniques, are found to facilitate the students’ abstract thinking prior to writing and assist the higher order thinking skill for better writing outcomes. It is suggested that pre-writing techniques should be a regular practice especially for low proficient student writers, with each technique serving different purposes.Keywords:argumentative writing, clustering, outlining, pre-writing techniques